Big cats - Turnbull, Stephanie; Francis, Neil Woodcock, John (Usborne London, 2008)
A simple presentation of the physical characteristics, habitat, and life cycle of some of our big cats such as leopards, tigers and pumas. This book also lists internet-links throughout that can be used with the book if you choose